Causes of rhabdomyolysis in acute poisonings - Janković, Snežana; Jović Stošić, Jasmina; Vučinić, Slavica; Perković Vukčević, Nataša; Vuković Ercegović, Gordana (Vojnosanitetski pregled, 2017)
Background/Aim. Rhabdomyolysis (RM) is potentially lethal syndrome, but there are no enough published data on its frequency and characteristics in acute poisonings. The aim of this study was to determine the causes and severity of RM in acute poisonings. Methods. Patients hospital charts were retrospectively screened during a one-year period in order to identify patients with RM among 656 patients treated due to acute poisonings with different agents. All the patients with RM were selected. Entrance criterion was the value of creatine kinase (CK) over 250 U/L. The severity of RM was assessed according to the Poison Severity Score. The patients were divided into three groups: the first one with mild RM (CK from 250 to 1,500 U/L), the second with moderate RM (CK from 1,500 to 10,000 U/L) and the third with severe RM (CK greater than 10,000 U/L). Results. RM occurred in 125 (19%) of the patients with acute poisonings. It was mainly mild (61%), or moderate (36%), and only in 3% of the patients was severe RM. The incidence of RM was the highest in poisonings with opiates (41%), pesticides (38%), neuroleptics (26%), anticonvulsants (26%), ethyl alcohol (20%), and gases (19%). Psychotropic agents were the most common causes of poisoning, and consequently of RM. Fatal outcomes were registered in 32 (25.60%) of all RM patients. The incidence of fatal outcomes in poisonings with mild, moderate and severe RM was 19.73%, 31.11% and 75%, respectively. Conclusion. RM syndrome occurs at a relatively high rate in acute poisonings. Although agent’s toxicity is crucial for the outcome, severe RM and its complications may significantly influence the clinical course and prognosis of poisoning. Routine analysis of CK, as a relevant marker for RM may indicate the development of RM in acute poisoning and initiate prompt therapeutic measures in preventing acute renal failure as the most frequent consequence of extensive rhabdomyolysis.